1998
DOI: 10.1103/physrevb.58.5498
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic structure factors in the Haldane phase of the bilinear-biquadratic spin-1 chain

Abstract: The excitation spectra of the Tϭ0 dynamic structure factors for the spin, dimer, and trimer fluctuation operators as well as for the center fluctuation operator in the one-dimensional Sϭ1 Heisenberg model with isotropic bilinear (J cos ) and biquadratic (J sin ) exchange are investigated via the recursion method for systems with up to Nϭ18 sites over the predicted range, Ϫ/4ϽՇ/4, of the topologically ordered Haldane phase. The four static and dynamic structure factors probe the ordering tendencies in the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 32 publications
3
50
0
Order By: Relevance
“…The period 3 phase -The existence of an extended critical phase with soft modes at k = ±2π/3 has first been reported in [18] and further analyzed and interpreted in [19,20,21]. Our results presented in the first part raise the question whether this critical region is of spin nematic character as well.…”
supporting
confidence: 59%
“…The period 3 phase -The existence of an extended critical phase with soft modes at k = ±2π/3 has first been reported in [18] and further analyzed and interpreted in [19,20,21]. Our results presented in the first part raise the question whether this critical region is of spin nematic character as well.…”
supporting
confidence: 59%
“…The initial conjecture concerning this gapless phase favored an almost "trimerized" ground state [68,69], featuring dominant singlet correlations involving three consecutive spins. Although models can be constructed which have exactly trimerized ground states [70,71], it was shown in [72] that these are not the dominant fluctuations in the standard bilinear-biquadratic model. It was realized only recently, by combining numerical simulations with earlier field-theoretical results [73], that the extended critical phase actually has dominant antiferroquadrupolar correlations [64].…”
Section: From Chains To the Square Latticementioning
confidence: 99%
“…This phase-including the frustration process leading to it-is reminiscent of the dimerized phase of the J 1 − J 2 spin 1/2 chain for J 2 / J 1 Ն 0.2411. 10 Initially a massive trimerized phase for the spin 1 Heisenberg chain ͑J 2 / J 1 =0͒ for / 4 Ͻ Ͻ / 2 was put forward, 11,12 but later works 6,7,[13][14][15][16] showed that the region remains massless and has dominant nematic correlations. In our model the additional next nearest neighbor coupling J 2 allows us to stabilize the trimerized state.…”
Section: Trimerized Phasementioning
confidence: 99%